O RATO COMO MODELO EXPERIMENTAL DO DIABETES - ESTUDO CLINICO-LABORATORIAL - Schellini, Silvana Artioli [UNESP]; Padovani, Carlos Roberto [UNESP]; Spadella, César Tadeu [UNESP]; Martins, J. L. [UNESP]; De Moraes Silva, M. A. [UNESP] (My University, 1995)
In this study, 90 Wistar rats were used. They were equally divided into three experimental groups - control group (CG), diabetic group (DG) and treated diabetic group (TG). The analyzed parameters were clinical (behavior, activity, general aspect, weight, water ingestion and diuresis) and biochemical (fasting glycemia and urinary glycosis). The diabetes was induced by alloxan and, then, treated with insulin associated to oral hypoglycemic (acarbosis). Observations were made at 5 experimental moments, as it follows: 1, 3, 6, 9, and 12 months after the diabetes induction. The results were submitted to variance analysis, with 5% of significance level. The DG presented lower weight and higher diuresis level than the CG and TG. The water ingestion of the CG was similar to TG. The glycemia levels were higher in DG than in CG, at every experimental moment. The TG, however, presented glycemia similar to the CG, except for the dosages at 3, and 9 months. They urinary glycosis of the DG and TG were similar between themselves, but higher than the one of the CG.
The rat as a model to experimental diabetes - A clinical and laboratory study
Keywords: alloxan; diabetes mellitus, experimental; rats inbred strains; acarbose; insulin; animal experiment; animal model; controlled study; diabetes mellitus; diuresis; female; fluid intake; glucose blood level; male; nonhuman; rat